2021
DOI: 10.1038/s41598-021-94947-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with hypertension according to JNC 7 and ACC/AHA 2017 guidelines in Bangladesh

Abstract: Most studies either followed Joint National Committee 7 (JNC 7) or World Health Organization-International Society of Hypertension (WHO-ISH) guidelines to ascertain the prevalence of hypertension among Bangladeshi adults. The American College of Cardiology/American Heart Association (ACC/AHA) revised the definition of hypertension in 2017, which has significant public health importance. In Bangladesh, the new guideline has resulted changes in prevalence and risk factors for hypertension compared to the JNC7 gu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 39 publications
(38 reference statements)
4
29
1
1
Order By: Relevance
“…39 A recent study found that the prevalence of prehypertension among Bangladeshi individuals aged 25 years and above is 31.9%. 20 Therefore, although most previous studies reported that older age groups have higher odds of having prehypertension and hypertension than their younger counterparts, 19,26,33,36,37 the current study proves the prevalence of hypertension and prehypertension among young adults are not as low as generally predicted. Our study shows that the prevalence of hypertension and prehypertension among young adults aged 31-34 years is almost similar to that among older adults.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…39 A recent study found that the prevalence of prehypertension among Bangladeshi individuals aged 25 years and above is 31.9%. 20 Therefore, although most previous studies reported that older age groups have higher odds of having prehypertension and hypertension than their younger counterparts, 19,26,33,36,37 the current study proves the prevalence of hypertension and prehypertension among young adults are not as low as generally predicted. Our study shows that the prevalence of hypertension and prehypertension among young adults aged 31-34 years is almost similar to that among older adults.…”
Section: Discussioncontrasting
confidence: 50%
“…The independent variables included in the study were selected based on previous literature reporting the risk of developing hypertension in populations of LMICs. 18,19,29,30,[33][34][35][36][37] The household-level factors included: administrative division (Barisal, Chittagong, Dhaka, Khulna, Mymensingh, Rajshahi, Rangpur, Sylhet), place of residence (urban, rural), and wealth status (poor, middle, rich). Socioeconomic and individual-level factors were: sex of participants (male, female), age of participants in years (18-20, 21-24, 25-30, 31-34), education level (no education, primary, secondary, higher), and occupational status (not working, working).…”
Section: Independent Variablesmentioning
confidence: 99%
“…High BMI and hypertension are important factors of diabetes reported in most of the previous studies 8 11 32 37 39 52 53. Our study findings also pointed out that with higher BMI have a greater likelihood of having diabetes compared with normal-weight adults in both 2011 and 2018 54–57…”
Section: Discussionsupporting
confidence: 69%
“… 8 11 32 37 39 52 53 Our study findings also pointed out that with higher BMI have a greater likelihood of having diabetes compared with normal-weight adults in both 2011 and 2018. 54–57 …”
Section: Discussionmentioning
confidence: 99%
“…The ACC/AHA 2017 definition increases this by 23 percentage points to half the population (51.5%), similar to increases of 26 and 21 percentage points reported for Bangladesh and China, respectively [7,9], indicating that adopting the newer definition is likely to increase HTN prevalence by one in four adults in most Asian developing countries, or double overall prevalence. Of those reclassified as hypertensive, 17% had history or symptoms consistent with CVD/PVD or diabetes.…”
Section: Discussionsupporting
confidence: 62%